Are There Any Differences in Urodynamic Studies Between Overactive Bladder Patients with Benign Prostatic Hyperplasia and Those without Benign Prostatic Hyperplasia? - Mahawong, Phitsanu; Yu, Cheong; Lam, Kin Man; Chu, Peggy Sau-kwan; Man, Chi-wai (The Thai Journal of Surgery, 2010)
Introduction: Overactive bladder and benign prostatic hyperplasia are quite common in middle age men. Some patients may have both of these conditions in the same time. Urodynamic study is still the most useful diagnostic test in this group of the patients because their lower urinary tract symptoms are unreliable. Objective: To compare results of urodynamic studies between overactive bladder patients with benign prostatic hyperplasia and overactive bladder patients without benign prostatic hyperplasia. Materials and Methods: From November 2007 to October 2009, 75 urodynamic studies were performed for male overactive bladder patients who were 40 years or older. The patients were retrospectively divided into two groups. Group I consisted of overactive bladder patients who also had been clinically diagnosed with benign prostatic hyperplasia, and Group II consisted of overactive bladder patients without benign prostatic hyperplasia. There were 41 patients in group I and 34 patients in group II. The results of the two groups were analyzed and compared. Results: There was a statistical difference only in terms of median post-void residual urine volume. Detrusor overactivities were demonstrated in 21/41(51.2%) patients of Group I and in 19/34 (55.9%) patients of Group II (P-value = 0.687). Nine patients in Group I (9/41; 21.9%) and eight patients in Group II (8/34; 23.5%) represented bladder outlet obstruction (P-value = 0.871). Impaired detrusor contractilities were found in only five patients of Group I (P = 0.060). Conclusions: The urodynamic results indicate that only the median post-void residual urine volume was statistically different between two groups of patients.